Experimental estimation of energy dissipated by multistorey post-tensioned timber framed buildings with anti-seismic dissipative devices - Felice Carlo Ponzo; Di Cesare Antonio; Lamarucciola Nicla; Domenico Nigro (Sustainable Structures, 2021)
The need to satisfy high seismic performance of structures and to comply with the latest worldwide policies of environmental sustainability is leading engineers and researchers to higher interest in timber buildings. A post-tensioned timber frame specimen was tested at the structural laboratory of the University of Basilicata in Italy, in three different configurations: i) without dissipation (post-tensioning only-F configuration); ii) with dissipative angles (DF- dissipative rocking configuration) and iii) with dissipative bracing systems (BF - braced frame configuration). The shaking table tests were performed considering a set of spectra-compatible seismic inputs at different seismic intensities. This paper describes the experimental estimation of energy dissipated by multistorey post-tensioned timber prototype frame with different anti-seismic hysteretic dissipative devices used in the DF and BF testing configurations. The main experimental seismic key parameters have also been investigated in all testing configurations.